2022
DOI: 10.5194/acp-22-12559-2022
|View full text |Cite
|
Sign up to set email alerts
|

Multi-axis differential optical absorption spectroscopy (MAX-DOAS) observations of formaldehyde and nitrogen dioxide at three sites in Asia and comparison with the global chemistry transport model CHASER

Abstract: Abstract. Formaldehyde (HCHO) and nitrogen dioxide (NO2) concentrations and profiles were retrieved from ground-based multi-axis differential optical absorption spectroscopy (MAX-DOAS) observations during January 2017–December 2018 at three sites in Asia: (1) Phimai (15.18∘ N, 102.5∘ E), Thailand; (2) Pantnagar (29∘ N, 78.90∘ E) in the Indo-Gangetic Plain (IGP), India; and (3) Chiba (35.62∘ N, 140.10∘ E), Japan. Retrievals were performed using the Japanese MAX-DOAS profile retrieval algorithm ver. 2 (JM2). The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 129 publications
1
7
0
Order By: Relevance
“…Studies based on satellite and ground observations showed that NO 2 levels in Tokyo decreased during the state of emergency (Ito et al 2021, Damiani et al 2022 but the changes that occurred on a daily scale were not examined. Figures 2(a) and (b) shows the time series of daily observations of surface NO 2 (red line) and partial column NO 2 (green line) and the respective meteorology-driven BAU scenarios during the first half of 2020, when mobility was strongly reduced (see supporting information for details of the datasets and ML approach).…”
Section: Aq Improvementsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies based on satellite and ground observations showed that NO 2 levels in Tokyo decreased during the state of emergency (Ito et al 2021, Damiani et al 2022 but the changes that occurred on a daily scale were not examined. Figures 2(a) and (b) shows the time series of daily observations of surface NO 2 (red line) and partial column NO 2 (green line) and the respective meteorology-driven BAU scenarios during the first half of 2020, when mobility was strongly reduced (see supporting information for details of the datasets and ML approach).…”
Section: Aq Improvementsmentioning
confidence: 99%
“…While the COVID-19 pandemic was a worldwide tragedy, it also created a global natural experiment enabling an evaluation of the impact of reduced anthropogenic emissions in urbanized areas, and thus the possibility of a 'green' future (e.g. Shakil et al 2020, Zheng et al 2020, Gkatzelis et al 2021, Laughner et al 2021, Cooper et al 2022, Damiani et al 2022. The mobility restrictions imposed by most governments reduced urban traffic (Yabe et al 2020) and improved AQ worldwide (Venter et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the method has known interferences from NO2 and O3 (Karst et al, 1993;Achatz et al, 1999;Tang et al, 2004), is not suitable for sampling in conditions with low relative humidities (Wisthaler et al, 2008;Uchiyama et al, 2009), and has had mixed results in comparison to research-grade observations (Hak et al, 2005;Dunne et al, 2018), making the accuracy of these inferred diel cycles difficult to determine. While other studies have demonstrated the feasibility for continuous measurements via various 55 spectroscopy-based methods (Yokelson et al, 1999;Cardenas et al, 2000;Dasgupta et al, 2005;Hak et al, 2005;Spinei et al, 2018;St Clair et al, 2019;Dugheri et al, 2021), the number of long-term (longer than 1 month), groundbased, continuous HCHO measurements is limited to a handful of studies, all of which employ either the multi-axial differential optical absorption spectroscopy measurement technique (Tian et al, 2018;Kumar et al, 2020;Hoque et al, 2022) or a proton-transfer-reaction mass spectrometer, for which HCHO measurements are sensitive to humidity 60 fluctuations (Warneke et al, 2013;Hansen et al, 2014).…”
mentioning
confidence: 99%